2008
DOI: 10.1016/j.jfe.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing determinants of forest owners’ decision-making using a sample selection framework

Abstract: A sample selection framework that simultaneously takes into account the two-step decisionmaking of forest owners (first whether or not to harvest, second the level of harvesting) is applied on representative cross-sectional data for forest properties and owners in Norway. Forest management plans, property size, forested area and income from agriculture are found to increase both the propensity to harvest and the harvesting levels. Income from engagement in other outfield-related productions and debt burden inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
6
22
1
2
Order By: Relevance
“…The literature review focussed on understanding the harvesting behaviour of forest owners (Beach et al, 2005;Bolkesjo et al, 2007;Butler, 2006;Favada et al, 2009;Stordal et al, 2008;Vokoun et al, 2006;Adams et al, 1991;Araño and Munn, 2006), as well as on wood supply in more general terms (Sterba et al, 2000;Verkerk et al, 2011). Based on our review and data availability for the entire study área, 16 potential location factors influencing the likelihood of harvest were identified, as well as a priori assumptions with regards to the direction of influence of each location factor on harvesting likelihood (Table 1).…”
Section: Location Factorsmentioning
confidence: 99%
“…The literature review focussed on understanding the harvesting behaviour of forest owners (Beach et al, 2005;Bolkesjo et al, 2007;Butler, 2006;Favada et al, 2009;Stordal et al, 2008;Vokoun et al, 2006;Adams et al, 1991;Araño and Munn, 2006), as well as on wood supply in more general terms (Sterba et al, 2000;Verkerk et al, 2011). Based on our review and data availability for the entire study área, 16 potential location factors influencing the likelihood of harvest were identified, as well as a priori assumptions with regards to the direction of influence of each location factor on harvesting likelihood (Table 1).…”
Section: Location Factorsmentioning
confidence: 99%
“…In Norvegia, è emerso che la gestione forestale è meno attiva se i proprietari hanno un'attività lavorativa extra-aziendale, risiedono lontano dalla proprietà e sono anziani (Løyland et al 1995). Ancora in Norvegia si è visto che la presenza di un piano di assestamento, la superficie totale e la frazione di superficie a bosco della proprietà, la presenza di fonti di reddito extra-aziendale, la giovane età del proprietario e la presenza di altre attività produttive condotte nella proprietà sono collegati positivamente con la predisposizione al taglio e con l'intensità di quest'ultimo (Størdal et al 2008). In Svezia sussistono differenze significative tra i proprietari che risiedono nella proprietà e quelli residenti altrove per gli aspetti produttivi ed economici, mentre non vi sono differenze statisticamente significative per gli aspetti collegati alla ricreazione e alla conservazione (Nordlund & Westin 2011).…”
Section: Determinanti Dei Comportamenti Dei Proprietari Forestaliunclassified
“…• applicazioni di analisi statistica multivariata (analisi fattoriale, cluster analysis, analisi delle componenti principali e altre) impiegate principalmente per ottenere le tipologie di classificazione dei proprietari forestali (Greene & Blatner 1986, Kuuluvainen et al 1996, Karppinen 1998a, Erickson et al 2002, Boon et al 2010 degli stessi, impiegati allo scopo di identificare i fattori determinanti dei comportamenti e delle attitudini gestionali ed ambientali dei proprietari (Jamnick & Beckett 1987, Romm et al 1987, Løy-land et al 1995, Lidestav & Ekström 2000, Størdal et al 2008, Joshi & Arano 2009, Boon et al 2010, Markowski-Lindsay et al 2011, Ficko & Boncina 2013); • modelli di scelta discreta, utilizzati per individuare la disponibilità ad accettare compensazioni monetarie volte a determinare un cambiamento positivo nel comportamento dei NIPFs nei confronti delle tematiche ambientali (Kline et al 2000, Horne 2006, Vedel et al 2013). …”
Section: Cenni Sulle Metodologie Utilizzateunclassified
“…It has also been identified as a key attribute in landowner forest management decisions [3,[8][9][10]. Since thoughtful planning is an important prerequisite to achieve optimum benefits, private forest landowners who often do not follow management plan recommendations are likely to underachieve such benefits [5].…”
Section: Introductionmentioning
confidence: 99%